Rekonstruksi Lembaga Pengadilan Menuju Indonesia Baru - Rusli Muhammad (Universitas Islam Indonesia, 2004)
The court (justice system) has noble duty and central position in a governanence, beside as a controller body, it is also as an institution which maintain law order in it's actualization in the real form. Meanwhile, this respectable position cannot be main tained properly and tends to deteriote as it shown by it's bad performances. There are three main problems appear, structural problem, legislation and human resources. Therefore the reconstruction of court system should be made by focusing on these problems.